Induced assembly of polystyrene composites for simultaneously improving flame retardant and electromagnetic shielding properties. (28th June 2021) - Gao, Caiqin; Shi, Yongqian; Zhu, Shicheng; Fu, Libi; Feng, Yuezhan; Lv, Yuancai; Yang, Fuqiang; Liu, Minghua; Shui, Wei
Abstract: Polystyrene/silicon wrapped ammonium polyphosphate/reduced graphene oxide (PS/SiAPP/rGO) composites with satisfactory flame retardant and electromagnetic interference (EMI) shielding properties were prepared by the approaches of filtration induced assembly and hot‐pressing. The results indicated that the SiAPP and rGO exhibited good dispersivity in the PS matrix. The introduction of the SiAPP and rGO promoted the thermal and fire‐safe performances of PS composites. Moreover, the peak of heat release rate and total heat release of the PS containing 10 wt% SiAPP and 10 wt% rGO were reduced by 47.2% and 30.3%, respectively. Meanwhile, the EMI shielding performance could reach 10 dB. It was proposed that that the SiAPP and rGO promoted the formation of more continuous and compact char residues besides the capture of free radicals, that is, H and OH which improved the flame retardant performance of PS. In addition, the multiple reflect and adsorption contributed to enhanced EMI shielding property. Therefore, the assembled PS/SiAPP/rGO system will offer a new approach to broaden the application of PS.